2003
DOI: 10.1002/jssc.200301480
|View full text |Cite
|
Sign up to set email alerts
|

Separation of diastereomers of flavanone‐7‐O‐glycosides by capillary electrophoresis using sulfobutyl ether‐β‐cyclodextrin as the selector

Abstract: Separation of diastereomers of flavanone-7-Oglycosides by capillary electrophoresis using sulfobutyl ether-b-cyclodextrin as the selector A method was developed for the separation of diastereomers of flavanone-7-O-glycosides by capillary electrophoresis using sulfobutyl ether-b-cyclodextrin (SBE-b-CD) in the background electrolyte. The effect of the concentration of the CD additive, buffer pH, and organic modifier on the migration times and resolution for five flavanone glycosides (naringin, hesperidin, neohes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…In spite of these advantages, application of chiral CE in food analysis is still at its infancy [3]. Table 3 shows the chiral-CE applications in food analysis found in the period covered by this review [24][25][26][157][158][159][160][161][162]. As can be seen in Table 3, cyclodextrins and their derivatives are the main chiral selectors used in CE and they have been applied to analyze different food compounds as amino acids, monoterpenes, catechins, flavanones and furanones.…”
Section: Chiral Analysis Of Food Compoundsmentioning
confidence: 99%
“…In spite of these advantages, application of chiral CE in food analysis is still at its infancy [3]. Table 3 shows the chiral-CE applications in food analysis found in the period covered by this review [24][25][26][157][158][159][160][161][162]. As can be seen in Table 3, cyclodextrins and their derivatives are the main chiral selectors used in CE and they have been applied to analyze different food compounds as amino acids, monoterpenes, catechins, flavanones and furanones.…”
Section: Chiral Analysis Of Food Compoundsmentioning
confidence: 99%
“…Other study has revealed the possibility to apply capillary electromigration methods to separate diastereomers of flavanone-7-O-glycosides [55]. Namely, authors demonstrated the usefulness of sulfobutyl ether-β-ciclodextrin (SBE-βCD, 7.5 mg/ml in buffer) as chiral selector in a 20 mM tetraborate (pH 7.0, 10 % methanol) running buffer to separate the diastereomers of narangin, hesperidin, neohesperidin, narirutin and eriocitrin standards [55].…”
Section: Other Flavonoidsmentioning
confidence: 99%
“…Several techniques have been reported for determination of diosmin in plant extracts, biological fluids and dosage forms, the majority of which are chromatographic in nature (Kanaze et al, 2003;Janeczko et al, 2003), in addition to capillary electrophoretic (Sawalha et al,2009;Aturki and Sinibaldi, 2003), electrochemical (El-Shahawi et al, 2006), spectrophotometric Mehra,1990) and spectrofluorimetric (Mohamed and Tawakkol, 2013) techniques meanwhile various analytical techniques were applied for the determination of rutin in raw material, pharmaceuticals and biological fluids and they include HPLC (Kuntic et al, 2007;Mauludin and Müller, 2009), voltammetry (Ensafi and Hajian, 2006;Volikakis and Efstathi, 2009) and spectrophotometry (Januja et al, 2009;Filtik et al, 2002).…”
Section: Introductionmentioning
confidence: 99%